2012
DOI: 10.1016/j.jorganchem.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Bioorganometallic chemistry of molybdenocene dichloride and its derivatives

Abstract: The potential application of metallocene complexes into the cancer research was established by the pioneer work of Köpf-Maeir and Köpf in the late 1970s. The combination of organometallic chemistry and biochemistry created a new research area: bioorganometallic chemistry. Bioorganometallic chemistry has developed rapidly in the last thirty years leading to application of organometallic species into diagnostic, sensors, immunoassays and anticancer research among others. This review focuses on the bioorganometal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 53 publications
2
30
0
Order By: Relevance
“…The redox behaviors of the new species can be attributed to the 3-hydroxy-4-pyronato ligands, which afford more aqueous stability to Cp 2 W(IV) than does chloride. Secondary chemical reactions and/or the formation of stable metal–oxo species may explain the irreversible redox behaviors of the new species [12, 21]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The redox behaviors of the new species can be attributed to the 3-hydroxy-4-pyronato ligands, which afford more aqueous stability to Cp 2 W(IV) than does chloride. Secondary chemical reactions and/or the formation of stable metal–oxo species may explain the irreversible redox behaviors of the new species [12, 21]. …”
Section: Resultsmentioning
confidence: 99%
“…Metallocene dichlorides were investigated in a series of tumor cell lines and those metallocenes containing titanium, molybdenum, vanadium, and niobium showed significant antitumor activity on Ehrlich ascites tumor, B16 melanoma, colon 38 carcinoma, and Lewis lung carcinoma cell lines [412]. Clinical trials were performed on Cp 2 TiCl 2 and showed that it has fewer secondary effects than cisplatin [13–18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Molybdocenes (Cp 2 MoX 2 ; Cp = cyclopentadienyl or η 5 ‐C 5 H 5 and derivatives, X = halide or pseudo halide) are water‐soluble Mo IV complexes whose aqueous chemistry has received much attention in order to investigate their possible use as an antitumor agent as well as their catalytic properties in organic synthesis and polymerization processes . Experimental studies on the coordination chemistry between Cp 2 MoCl 2 and different DNA (deoxyribonucleic acid) models allowed to propose that [Cp 2 Mo(OH)(OH 2 )] + is the dominant species at physiological pH and, therefore, the active species in chemical transformations catalyzed or mediated by Cp 2 MoCl 2 in water .…”
Section: Introductionmentioning
confidence: 99%